The importance of the aesthetic expression of the Islamic decoration in mosque and its application / Norzalifa Zainal Abidin and Mizan Hitam - Zainal Abidin, Norzalifa; Hitam, Mizan (2012)
This research discussed on the aesthetic expression of the Islamic decoration as applied in mosque interior. The true function of decoration in the Islamic Arts will be highlighted to obtain better understanding of its important application to the mosque interiors. By having a better understanding of its functions, designers and users will be able to apply and perceive these decoration in their true essence which relates to enhancing the Feeling of Remembrance of Allah as the tool for "Zikr‟, which is the key base for the Islamic doctrine. Furthermore, the true function of decoration will further enhance and accentuate the main function of mosque as an important Islamic building. By highlighting its importance and true functions, better understanding can be obtained to ensure the application of decoration in mosque to be aligned with the main functions of mosque.